War by contract human rights, humanitarian law, and private contractors - Francioni, Francesco; Ronzitti, Natalino (Oxford : Oxford University Press, 2011)
The conduct of armed conflict is increasingly being outsourced to private military and security companies, whose legal position remains unclear. This book identifies and analyses the human rights and humanitarian law framework applicable to these companies, examining how they can be held to account and how victims can obtain remedies.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Humanitarian law; Private military companies